Annual growth ring formation and growth rates of different tree functional types in a tropical mountain forest in Ethiopia - Bräuning, Achim; Krepkowski, Julia; Hiltner, Ulrike; Gebrekirstos, Aster (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 12: Proceedings of the DENDROSYMPOSIUM 2013 Scientific Technical Report STR14/05, GFZ Potsdam, 2014)

Impacts of precipitation variability on the dynamics of a dry tropical montane forest - Hiltner, Ulrike; Bräuning, Achim; Gebrekirstos, Aster; Huth, Andreas; Fischer, Rico (Ecological Modelling, 2016)
Ecosystem structures of tropical mountain forests are under threat due to changes in climate and land-use. The dry tropical montane forest of Munessa-Shashemene in south-east Ethiopia is a prominent example of degradation and deforestation in the sub-humid tropics. In recent years an increasing number of precipitation events has been observed, mainly during the short rainy season. Moreover, the recent IPCC Report envisages an increase in total annual precipitation, accompanied by more frequent extreme weather events (drought, torrential rains) for the Horn of Africa until the end of the 21st century.To evaluate possible consequences for local forest ecosystems, we applied the process-based, individual-oriented forest simulation model Formix3 to identify the influence of precipitation variability on the forest growth dynamics. We parameterised the model using field observation data including, for the first time, a tree-ring chronology of Croton macrostachyus. By using different levels of annual precipitation and intra-annual precipitation patterns, we analysed explicit simulation scenarios focussing on both overall and species-specific aboveground biomass dynamics and tree species composition.We found that the model reproduces aboveground biomass productivity precisely under current precipitation conditions. Variations in precipitation cause ecological shifts in the conditions for tree growth. Biomass and species richness both increase with mean annual precipitation, with the effects stabilising over time. Our results emphasise the impact of the duration and frequency of periods of water limitation on forest structure and growth.Our model has a variety of potential applications including investigation of the impacts of precipitation variability on forest structure and tree species diversity. It is thus a useful tool for extrapolating local growth measurements and succession, and analysing the impact of different management strategies on dry tropical montane forests.
Keywords: Climate change simulation; Dry tropical montane forest; Ethiopia; Forest growth model; Formix3; Tree-ring measurement

Importance of the forest state in estimating biomass losses from tropical forests: combining dynamic forest models and remote sensing - Hiltner, Ulrike; Huth, Andreas; Fischer, Rico (Biogeosciences, 2022)
Disturbances, such as extreme weather events, fires, floods, and biotic agents, can have strong impacts on the dynamics and structures of tropical forests. In the future, the intensity of disturbances will likely further increase, which may have more serious consequences for tropical forests than those we have already observed. Thus, quantifying above-ground biomass loss of forest stands due to stem mortality (hereafter biomass loss rate) is important for the estimation of the role of tropical forests in the global carbon cycle. So far, the long-term impacts of altered stem mortality on rates of biomass loss have not been adequately described.
CRIS-Team WoS Importer:2022-04-15